Young entrepreneurs in the food business during and after the community quarantine phase of the COVID-19 pandemic - Bacud, Kenneth Christian (College of Home Economics, University of the Philippines Diliman, 2023)
The COVID-19 pandemic posed unprecedented challenges to food business owners, including young entrepreneurs. This research examined the experiences of 20 young entrepreneurs in the Philippines during and after the community quarantine. Through qualitative methods, including in-depth interviews, the study explored their challenges, adaptation strategies, and support systems. The challenges faced by young entrepreneurs included decrease in revenue, financial struggles, supply chain disruptions, limited government assistance, and health protocol changes. However, they also experienced benefits such as increased demand for online food delivery and social media presence. Young entrepreneurs demonstrated resilience by adapting to online platforms, engaging customers through promotions, and utilizing social media. Support systems, particularly from family and friends, played a crucial role in their success. Motivations for young entrepreneurs included passion for food, entrepreneurial independence, and financial success. This research provided valuable insights into the experiences of young entrepreneurs during and after the pandemic, informing future initiatives to support their growth and success in a changing business landscape.